Asociación del indice predictivo de asma y presencia de la enfermedad en niños que acuden a consulta externa del Hospital Infantil “Alfonso Villagomez” Riobamba, en el periodo diciembre 2017 – abril 2018 - Narciza Manuela, Guamán Guzmán (2018)
This study was conducted at Children's Hospital Alfonso Villagomez in the city of Riobamba, with extern patients, during the period December 2017 - April 2018. Asthma is a chronic inflammation of airways having recurrent episodes of symptoms caused by bronchial obstruction and hyperreactivity of the airways manifesting wheezing, breathlessness, chest tightness and coughing, particularly at night, causing varying airflow obstruction, occurring spontaneously to determine the association rate of asthma and predictive presence of disease in children treated at outpatient Alfonso Villagomez Children's Hospital in the period from December 2017 - April 2018. Materials and Methods: The present work was performed by the prospective methodology, descriptive of transverse and analytical cut. Results: The survey was applied considering the sample of 337 children identified at 2724 children who were the population who attended to the external service at Alfonso Villagomez Children's Hospital during the period December 2017 April 2018. We proceeded to perform the analysis of the criteria of predictive Index asthma for the development of the disease reaching an outcome predictive positive rate of asthma in 189 children, corresponding at 56% of the total population study for the development of the disease and obtaining a negative predictive index of asthma a total of 148 patients with at 44%.